DIF in the Spanish Version of the Verbal Selective Reminding Test Using Samples From Hispanics in the United States, Mexicans, and Spaniards - Morales-Ortiz, Manuel; Peña-Cardenas, Fabiola (Frontiers in Psychology, 2019)
Aim Before a test can be used in the target population, it is necessary to demonstrate that there is measurement equivalence. One way to do this is by studying differential item functioning (DIF). Objective In this study, we used the Mantel–Haenszel procedure and logistic regression to analyze DIF in the Spanish version of the Verbal Selective Reminding Test between Spaniards, Mexicans, and Hispanics in the United States. Method Three balanced samples, matched by age, education, and sex, were studied: Spaniards, Mexicans, and Hispanics [616 healthy participants from Spain (n = 211), Mexico (n = 201), and the United States (n = 205)]. A six-trial version of the Spanish version of the Verbal Selective Reminding Test was administered and scored according to standard procedures. Results Statistical analysis showed some DIF between the samples of Spaniards, Mexicans, and Hispanics. A bootstrap validation of results confirmed that the item pollo showed DIF: the Mexicans and Hispanics outperformed the Spaniards, holding a total score constant. The item oído also showed DIF and was remembered in greater measure by the Spaniards. Conclusion The Spanish version of the Verbal Selective Reminding Test can be used with Hispanic populations.